Incidence and conditions of musculoskeletal injuries in elite Spanish tennis academies: a prospective study - Moreno-Pérez, V.; Hernández-Sánchez, S.; Fernandez-Fernandez, J.; Del Coso, J.; Vera-Garcia, F. J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Injuries are a major adverse event in a tennis player`s career. Reducing injury requires a thorough knowledge of the epidemiology of tennis injuries. The aim of this study was to report the incidence and conditions of musculoskeletal injuries in elite tennis players. METHODS: The medical staff of 162 tennis players recorded the type and conditions of musculoskeletal injuries for one season in accordance with a consensus statement. Other information such a training hours and competitive games played was also recorded. RESULTS: A total of 199 injuries were recorded, equivalent to an overall incidence of 1.03 injuries per 1000 played games and 1.25 per 1000 h of training. Lower limbs were the most common injury location in male players (38.3%) and the trunk in females (41.3%) although muscle/tendon injuries were the most common type in both groups. There was a higher percentage of gradual-onset injuries (61.4%) than acute injuries (38.6%). The injury incidence on clay courts was 1.53±2.85 and 1.11±1.29 injuries per 1000 played games in males and females, respectively. The majority of the gradual-onset injuries were reported in the upper limbs (45.9%) while acute injuries were mostly located in the lower limbs (68.8%). During match exposure, the trunk was the most common location of injury (36.8%) while the lower limbs were the most common location of injury during training (41.7%). CONCLUSIONS: In elite tennis, a high percentage of musculoskeletal injuries were located in the lower limbs in males and in the trunk in females, occurred during matches and affected muscles or tendon structures. However, the type of the injury is influenced by different conditions such as the type of exposure (match vs. training) or the mechanism of injury (acute vs. gradual-onset). This information suggests that an early focus should be placed on the monitoring of the workload and changes in court surface during a season.